2015
DOI: 10.1017/s0022215115001747
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between neutrophil-to-lymphocyte ratio and obstructive sleep apnoea syndrome

Abstract: Neutrophil-to-lymphocyte ratio may be used to determine disease severity, complementing polysomnography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…1 Therefore, in our study, there was no difference between the body mass indices and mean ages of the groups ( p = 0.20 and p = 0.415 respectively). The neutrophil-to-lymphocyte ratio is now accepted as a significant predictor of adverse clinical outcomes, and various studies have found neutrophil-to-lymphocyte ratio to be a reliable biomarker in oncology, 2,3 cardiology, 4,5 and several other diseases accompanied by systemic inflammation such as Alzheimer's disease, ulcerative colitis, appendicitis and chronic kidney disease.…”
mentioning
confidence: 43%
See 1 more Smart Citation
“…1 Therefore, in our study, there was no difference between the body mass indices and mean ages of the groups ( p = 0.20 and p = 0.415 respectively). The neutrophil-to-lymphocyte ratio is now accepted as a significant predictor of adverse clinical outcomes, and various studies have found neutrophil-to-lymphocyte ratio to be a reliable biomarker in oncology, 2,3 cardiology, 4,5 and several other diseases accompanied by systemic inflammation such as Alzheimer's disease, ulcerative colitis, appendicitis and chronic kidney disease.…”
mentioning
confidence: 43%
“…For this reason, more studies have been conducted in recent years examining the association of neutrophil-to-lymphocyte ratio with inflammation. [1][2][3][4][5][6][7][8][9] The results of our study demonstrated that the neutrophilto-lymphocyte ratio values had a positive correlation with the severity of obstructive sleep apnoea syndrome (OSAS). …”
mentioning
confidence: 99%
“…These findings support the opinion that as obesity levels increase inflammation also increases. In a study by Yenigun et al a positive correlation was found between the severity of OSAS and NLR and it was also shown that as AHI increased NLR also increased (27).…”
Section: Discussionmentioning
confidence: 87%
“…Yenigun A et al evaluated the relationship between OSAS and NLR and found a positive correlation between NLR and AHI in patients with OSAS (22). In another study done in patients with metabolic syndrome showed increased NLR (23).…”
Section: Discussionmentioning
confidence: 99%